Digitalisasi Pencatatan Keuangan UMKM OO Trans melalui Penerapan MYOB Accounting - S, Suharyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Digital transformation in financial recordkeeping has become an urgent necessity for Micro, Small, and Medium Enterprises (MSMEs), particularly in the transportation sector which involves high transaction intensity. This study aims to analyze the implementation of MYOB (Mind Your Own Business) accounting software in OO Trans, an MSME operating in the transportation services sector. Prior to digitalization, financial records were maintained manually using Microsoft Excel, which tended to be inefficient and lacked integration. Employing a descriptive-qualitative method, this research collected data through observation, interviews, documentation, and financial data analysis for the year 2024. The results show that the adoption of MYOB significantly improved the accuracy and efficiency of financial recording. In 2024, OO Trans recorded a total revenue of IDR 82,013,000 and fuel (BBM) expenses totaling IDR 46,405,000. The average monthly revenue was IDR 6,834,417, while the average monthly fuel expense was IDR 3,867,083. Through the MYOB system, the MSME was able to generate real-time income statements and facilitate business performance analysis. Furthermore, digital financial records enhance transparency, accountability, and open up access to financing opportunities.